Cognitive Performance Patterns in Healthy Individuals with Substantia Nigra Hyperechogenicity and Early Parkinson’s Disease - Yilmaz, Rezzak; Gräber, Susanne; Roeben, Benjamin; Suenkel, Ulrike; Thaler, Anna-Katharina von; Heinzel, Sebastian; Metzger, Florian G.; Eschweiler, Gerhard W.; Maetzler, Walter; Berg, Daniela; Liepelt-Scarfone, Inga (Frontiers in Aging Neuroscience, 2016)
Introduction: Hyperechogenicity of the substantia nigra (SN+) is a risk marker for Parkinson’s disease (PD) which can be detected before the diagnosis. In healthy individuals, SN+ has been associated with slight deficits in specific cognitive functions, suggesting cognitive impairment as a possible pre-diagnostic marker for PD. However, the pattern of cognitive deficits associated with SN+ has not yet been compared with those present in PD. Methods: Data of 262 healthy individuals with normal echogenicity (SN-) and 48 healthy individuals with SN+ were compared with 82 early stage PD patients using the “Consortium to Establish a Registry for Alzheimer’s disease” test battery. First, the test clusters (factors) were identified using a principal component analysis (PCA). Mean group performance of cognitive tests belonging to distinct factors, according to the PCA, and single subtest performances were compared using analyses of variance. Second, the number of individuals with abnormal cognitive performances (z-score <-1.0) were compared between groups. Results: Verbal memory, semantic and executive function, and praxis were identified as components of cognitive performances. The SN+ group performed significantly worse than the SN- group in tests assessing semantic and executive function, with a non-significant decrease in verbal memory. On the subtest level, individuals of the SN+ group scored significantly lower than the SN- group on the Boston Naming Test (BNT) (p=0.008). In all subtests, the percentages of PD patients with values below the cut-off for abnormal performance were higher than in the SN- group. Moreover, more individuals from the SN+ group scored below the cut-off in the BNT (SN-=8.4%, SN+=20.8%, p=0.01) and TMT-B (SN-=6.9%, SN+=16.7%, p=0.02), compared to the SN- group. Conclusion: This study confirms poorer performance of healthy individuals with SN+ compared to SN- in specific cognitive domains. However, against the SN- group, the cognitive profile of the SN+ group was not fully consistent with the profile of early PD patients. Our data argues that cognitive impairment associated with SN+ might differ slightly from that seen in early PD. Compensational mechanisms in the early phases of neurodegeneration, and the fact that only a subgroup of SN+ will develop PD, may partly explain these differences.